Alzheimer’s disease: Pathophysiology and dental pulp stem cells therapeutic prospects - Xiong, Wei; Liu, Ye; Zhou, Heng; Jing, Shuili; He, Yan; Ye, Qingsong (Frontiers in Cell and Developmental Biology, 2022)
Alzheimer’s disease (AD) is a destructive neurodegenerative disease with the progressive dysfunction, structural disorders and decreased numbers of neurons in the brain, which leads to long-term memory impairment and cognitive decline. There is a growing consensus that the development of AD has several molecular mechanisms similar to those of other neurodegenerative diseases, including excessive accumulation of misfolded proteins and neurotoxic substances produced by hyperactivated microglia. Nonetheless, there is currently a lack of effective drug candidates to delay or prevent the progression of the disease. Based on the excellent regenerative and reparative capabilities of stem cells, the application of them to repair or replace injured neurons carries enormous promise. Dental pulp stem cells (DPSCs), originated from ectomesenchyme of the cranial neural crest, hold a remarkable potential for neuronal differentiation, and additionally express a variety of neurotrophic factors that contribute to a protective effect on injured neuronal cells. Notably, DPSCs can also express immunoregulatory factors to control neuroinflammation and potentiate the regeneration and recovery of injured neurons. These extraordinary features along with accessibility make DPSCs an attractive source of postnatal stem cells for the regeneration of neurons or protection of existing neural circuitry in the neurodegenerative diseases. The present reviews the latest research advance in the pathophysiology of AD and elaborate the neurodifferentiation and neuroprotective properties of DPSCs as well as their application prospects in AD.